Early thoracoscopic plication of diaphragm in a newborn with brachial plexus palsy and concurrent phrenic nerve palsy - Saurabh Shyam Garge; Gouri Rao Passi; Devendra Ghanekar (Wolters Kluwer Medknow Publications, 2017)
Phrenic nerve palsy is a rare cause of respiratory distress in a newborn. When conservative measures fail to achieve adequate ventilation, then early surgical plication has been found to be associated with good outcome. We report a case of neonate with phrenic nerve palsy in whom an early thoracoscopic diaphragmatic plication was done.